Flavone constituents of Phlomis bruguieri Desf. with cytotoxic activity against MCF-7 breast cancer cells - Seyed Ebrahim Sajjadi; Zeinab Delazari; Mahmoud Aghaei; Mustafa Ghannadian (Wolters Kluwer Medknow Publications, 2018)
Phlomis bruguieri (P. bruguieri) is a large genus in the Lamiaceae family, with a wide variety distributed in Euro-Asia, Central Asia, Iran, and China. Phlomis flowers have been used as herbal tea for gastrointestinal disturbances, protection of liver and cardiovascular systems. The aim of this study was to analyse phytochemical of flavonoid constituents in semi polar fraction of P. bruguieri. Methanol extract of plant material (4 kg) yielded 361 g dark green concentrated extract gum. After preliminary fractionation by normal column chromatography on silica gel, Fr. 2 eluted with chloroform: methanol (90:10) selected as semi polar fraction and was more purified using different chromatography columns on silica gel, polyamide SC6 and Sephadex LH-20 adsorbents. Finally one new and three known flavonoids (1-4) were characterized in semi polar fraction. Isolated structures were identified using 1H-NMR, 13C-NMR, 31P-NMR, HSQC, HMBC, negative ESI mass, and UV spectra using different shift reagents. Using standard MTT assay, cytotoxicity of isolated new compound was done against michigan cancer foundation-7 (MCF-7) breast cancer cells. Phytochemical analysis of P. bruguieri resulted in identification of one new 4'-methoxy-luteolin-7-phosphate and three known flavones including luteolin, apigenin, and tricin for the first time in this plant. In MTT cytotoxicity test, 4'-methoxy-luteolin-7-phosphate showed cytotoxicity with IC50 value of 43.65 ± 8.56 μM agasint MCF-7 breast cancer cells.